1994
DOI: 10.1093/ajcn/59.3.612
|View full text |Cite
|
Sign up to set email alerts
|

Effect of consumption of whole milk and skim milk on blood lipid profiles in healthy men

Abstract: A controlled crossover feeding study was conducted in eight males aged 20-36 y to compare the effects of skim milk and whole milk on blood lipids. For 6-wk diet periods, 236 mL/4191 kJ of skim or whole milk was consumed with a background diet designed according to the American Heart Association recommendations. Plasma lipids were analyzed at baseline and at 3 and 6 wk. After 6 wk, the mean total cholesterol concentration was 4.47 mmol/L with skim milk and 4.80 mmol/L with whole milk (P < or = 0.001); mean low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 44 publications
2
33
0
Order By: Relevance
“…Previous intervention studies examining the effects of milk supplementation or increased dairy consumption on lipid concentrations have produced varying results, which are likely due to differences in the amount and fat composition of the milk (or dairy product) used, participant characteristics, study duration and/or whether the intervention was combined with weight loss or a low-fat diet (Buonopane et al, 1992;Steinmetz et al, 1994;Barr et al, 2000;Zemel et al, 2004). Our findings are consistent with a 12-week trial that found that advice to drink three glasses of skim or fat-reduced milk per day did not change any lipid parameter in older men and women (Barr et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Previous intervention studies examining the effects of milk supplementation or increased dairy consumption on lipid concentrations have produced varying results, which are likely due to differences in the amount and fat composition of the milk (or dairy product) used, participant characteristics, study duration and/or whether the intervention was combined with weight loss or a low-fat diet (Buonopane et al, 1992;Steinmetz et al, 1994;Barr et al, 2000;Zemel et al, 2004). Our findings are consistent with a 12-week trial that found that advice to drink three glasses of skim or fat-reduced milk per day did not change any lipid parameter in older men and women (Barr et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to these negative claims, several studies increased the knowledge concerning the nutritional value and characteristics of milk, showing that it can be considered a multifunctional food product. Besides providing proteins, lipids, vitamins and minerals (Steinmetz et al, 1994;Atti et al, 2006;Collomb et al, 2008;Descalzo et al, 2012), recent research has shown that some milk fatty acids (FAs), particularly conjugated linoleic acid (CLA), have further beneficial effects on the health status of people by exhibiting anti-carcinogenic, anti-diabetic and anti-inflammatory benefits (Gavino et al, 1999: Khanal & Dhiman, 2004. The Jersey breed is popular among pasture-based dairy farmers, especially in the Southern Cape area of South Africa (Muller et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Milk intake is probably positively related to blood lipid levels (Steinmetz et al, 1994;Nagaya et al, 1996), but the effect shown in many studies is either trivial or absent (Shaper et al, 1991;Jacobsen & Stensvold, 1992;D'Avanso et al, 1995;Abbott et al, 1996;Onning et al, 1998;Barr et al, 2000;Ness et al;Elwood et al, 2003). In fact, in some studies a milk supplement led to a decrease in blood lipids (Buonapane et al, 1992;St Onge et al, 2000;Samuelson et al, 2001), leading again to the suggestion that milk may contain substances that counterbalance any expected positive effect on lipid levels (Pfeuffer & Schrezenmeir, 2000).…”
Section: Introductionmentioning
confidence: 99%